Economic developments in the ancient Kingdom of Meroe and its role in sustainable development during the period (644-1 BC) - Dr. Dhafar Nima Aylan (Journal of College of Education, 2025)
This study explores the economic developments in the Kingdom of Meroë and their role in achieving sustainable development during the period (644–1 B.C.), through seven main axes. The first axis highlights the geostrategic location of Meroë and its contribution to agricultural and commercial growth, especially after the capital shifted from Napata to Meroë due to fertile lands and favorable climatic conditions. The second axis examines agriculture, where the Meroitic civilization developed irrigation techniques and diversified crop production along the Nile Valley. The third axis discusses the importance of animal resources, which provided food, clothing, and labor for irrigation, alongside fishing and hunting. The fourth axis addresses Meroitic industries, including iron production, pottery, textiles, glassmaking, and boatbuilding. The fifth axis focuses on mining, particularly the extraction of gold, copper, bronze, and iron. The sixth axis investigates the flourishing internal and external trade, with Meroë controlling caravan routes and exporting African commodities such as ivory, ebony, ostrich feathers, and gum, while importing Egyptian pottery, glassware, and luxury goods. The seventh axis highlights the role of transportation, where caravans relied on donkeys and horses, and trade routes linked Meroë with Egypt and sub-Saharan Africa.The research concludes that the Kingdom of Meroë represented a pioneering model of economic organization, integrating agriculture, industry, mining, trade, and transportation into a system that supported the foundations of sustainable development.
Keywords: Marwa, economy, development , industries, trade